Incorporation of leek powder (Allium ampeloprasum var. porrum) in wheat bread: Technological implications, shelf life and sensory evaluation. (January 2022) - Bernaert, Nathalie; Debonne, Els; De Leyn, Ingrid; Van Droogenbroeck, Bart; Van Bockstaele, Filip
Abstract: In this study, the incorporation of leek in wheat bread was explored. Green leek leaves were dried with two techniques to obtain leek powder after milling. The air-dried and freeze-dried powders were incorporated into wheat flour at five substitution levels (0, 0.5, 1, 1.5 and 2 g/100 g). The impact of leek powder on dough rheology, bread quality, sensory evaluation and mould-free shelf-life was investigated. Leek powder negatively impacted the mixing properties and significantly changed the viscoelastic properties of the wheat flour dough. At low levels, the dough was strengthened whereas at higher levels both dough resistance as extensibility decreased. Bread quality was also affected, resulting in lower bread volume and coarser crumb structure. The negative impact on dough and bread properties was more pronounced for freeze-dried powder. The result of the sensory study showed that wheat flour could be fortified by 1 g/100 g of leek powder without adverse effect on the consumer acceptability. Finally, the addition of leek powder did not impact the mould-free shelf-life of wheat bread. Highlights: Green leek leaves were either air- or freeze-dried, to obtain leek powder after milling. Leek powder negatively impacted the mixing properties by increased dough stickiness. Lower bread volume and coarser crumb structure were obtained with leek powder. The impact on dough properties was more pronounced for freeze-dried leek powder. Maximal 1 g air-dried powder per 100 g flour can be supplemented without side-effects.